32. THE CURRENT QUALITY OF LIFE OF TYPE 2 DIABETES PATIENTS ON INSULIN THERAPY AT THE INSTITUTE FOR SENIOR OFFICERS TREATMENT – 108 CENTRAL MILITARY HOSPITAL, 2025. (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the quality of life (QoL) of type 2 diabetes patients on insulin therapy at the Institute for Senior Officers Treatment – 108 Central Military Hospital in 2025.Subjects and methods: A cross-sectional descriptive study was conducted on 150 patients with type 2 diabetes from January to June 2025. QoL was assessed using the AsianDQOLResults: The mean QoL score was 64.1 ± 7.3 (95%CI: 62.9–65.3). Classification showed 58.0% of patients had fair QoL, 18.0% good/excellent, 20.0% low-average, and 4.0% poor. Among the five domains, personal relationships scored the lowest (33.3 ± 12.6), followed by diet (47.0 ± 12.9) and physical health (55.0 ± 19.4). Mental health (83.0 ± 15.9) and financial status (90.4 ± 9.8) scored higher.Conclusions: The QoL of insulin-treated type 2 diabetes patients was generally fair but limited in personal relationships, diet, and physical health. These findings suggest further studies and interventional trials are needed to improve QoL in this patient group.
Keywords: Quality of life; Type 2 diabetes; Insulin; AsianDQOL.